1987
DOI: 10.1093/ptj/67.8.1191
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inherent Muscle Length on Isometric Plantar Flexion Torque in Healthy Women

Abstract: This study investigated the relationship between inherent muscle length and torque production in 59 healthy women. We recorded nondominant ankle range-of-motion values for each subject. These values were partitioned into quartiles for two knee positions. Women with "loose" plantar flexor muscles comprised the first quartile, and those with "tight" plantar flexor muscles the fourth quartile. Tight- and loose-muscle groups were established for the 0-degree (fully extended) and 90-degree (flexed) knee test positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…The magnitude of T max/A obtained in a locked-unit mechanical configuration and with a 1D force sensor (100.5 ± 19.1 N m) was comparable with those of previous studies of young adults in the same ankle and knee positions (Hornsby et al 1987;Mademli et al 2004;Simoneau et al 2007;Turpin et al 2014). However, T max 1D/A values obtained with an open-unit mechanical configuration were significantly lower (P < 0.001) (~60 %) than those obtained with the classical locked-unit configuration.…”
Section: Discussionsupporting
confidence: 87%
“…The magnitude of T max/A obtained in a locked-unit mechanical configuration and with a 1D force sensor (100.5 ± 19.1 N m) was comparable with those of previous studies of young adults in the same ankle and knee positions (Hornsby et al 1987;Mademli et al 2004;Simoneau et al 2007;Turpin et al 2014). However, T max 1D/A values obtained with an open-unit mechanical configuration were significantly lower (P < 0.001) (~60 %) than those obtained with the classical locked-unit configuration.…”
Section: Discussionsupporting
confidence: 87%
“…The active and/or passive stretching of the gastrocnemius muscle is the main factor to control the ankle dorsi flexion [ 62 ], which, in turn, is suggested to be the determining factor for the optimization of the vertical squat jump performance [ 56 ]. The present findings can be interpreted under the perspective that the alteration of the angular position of the examined joints result in changes in the length of the gastrocnemius muscle and eventually to the function of its musculotendinous unit [ 47 , 50 , 63 , 64 ] and the neuromechanical function of the ankle joint flexors and extensors [ 65 , 66 , 67 , 68 , 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present findings can be interpreted under the perspective that the alteration of the angular position of the examined joints result in changes in the length of the gastrocnemius muscle and eventually to the function of its musculotendinous unit [ 47 , 50 , 63 , 64 ] and the neuromechanical function of the ankle joint flexors and extensors [ 65 , 66 , 67 , 68 , 69 , 70 ]. It is suggested that these modifications due to the different ankle angle cause alterations in the force application capabilities of the shank muscles, as well as in the transfer of the power [ 62 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ]. If constrains exist when executing a vertical squat jump, either in the form of ankle mobility reduction [ 55 ] or the demand for a full feet contact [ 78 ], then several adaptations occur as the muscle activation patterns are adjusted for the maximization of the jump height from the altered initial posture [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ankle dorsi flexion, which is the initial position of the ankle joint for a vertical squat jump, is affected by the extension rather than by the flexion of the knee joint as a result of the bi-articularity of the gastrocnemius muscle [69]. In addition, it is suggested that the active and passive lengthening of the gastrocnemius muscle is the major factor for controlling ankle dorsi flexion [70]. Thus, the altered angular position of the lower limb joints causes differentiation in the strength application capabilities of the shank muscles, as well as in the proximal-to-distal transfer of energy [71][72][73][74][75], which corresponds to the body segment sequencing for the execution of the handball throws [47,76,77].…”
Section: Discussionmentioning
confidence: 99%